Tailoring Perovskite Adjacent Interfaces by Conjugated Polyelectrolyte for Stable and Efficient Solar Cells. Issue 5 (25th February 2020) - Li, Bowei; Xiang, Yuren; Jayawardena, K. D. G. Imalka; Luo, Deying; Watts, John F.; Hinder, Steven; Li, Hui; Ferguson, Victoria; Luo, Haitian; Zhu, Rui; Silva, S. Ravi P.; Zhang, Wei
Abstract : Interface engineering is an effective means to enhance the performance of thin‐film devices, such as perovskite solar cells (PSCs). Herein, a conjugated polyelectrolyte, poly[(9, 9‐bis(3′‐(( N, N ‐dimethyl)‐ N ‐ethyl‐ammonium)‐propyl)‐2, 7‐fluorene)‐alt‐2, 7‐(9, 9‐dioctylfluorene)]di‐iodide (PFN‐I), is used at the interfaces between the hole transport layer (HTL)/perovskite and perovskite/electron transport layer simultaneously, to enhance the device power conversion efficiency (PCE) and stability. The fabricated PSCs with an inverted planar heterojunction structure show improved open‐circuit voltage ( V oc ), short‐circuit current density ( J sc ), and fill factor, resulting in PCEs up to 20.56%. The devices maintain over 80% of their initial PCEs after 800 h of exposure to a relative humidity 35–55% at room temperature. All of these improvements are attributed to the functional PFN‐I layers as they provide favorable interface contact and defect reduction. Abstract : A conjugated polyelectrolyte is used for simultaneously tailoring the perovskite adjacent interfaces. Herein, for the first time, poly[(9, 9‐bis(3′‐(( N, N ‐dimethyl)‐ N ‐ethyl‐ammonium)‐propyl)‐2, 7‐fluorene)‐alt‐2, 7‐(9, 9‐dioctylfluorene)]di‐iodide (PFN‐I)is exploited in inverted planar perovskite solar cells. At the hole transport layer/perovskite interface, the PFN‐I is beneficial for solving the dewetting issue. At the perovskite/electron transport layer interface, the PFN‐I is advantageous for passivating defects.